Role of previously formed corrosion product layers on sulfide-assisted corrosion of iron archaeological artefacts in soil. (December 2017) - Rémazeilles, C.; Neff, D.; Bourdoiseau, J.A.; Sabot, R.; Jeannin, M.; Refait, Ph.
Highlights: Archaeological artefacts can be used as representative of aged mild steel structures. Dense corrosion product layers of FeCO3 act as protective barrier against sulfide. The reactivity of FeCO3 towards sulfide induces its transformation into FeS. Abstract: Iron archaeological nails (16th century) were used as representative of the mild steel structures envisaged for the storage of nuclear waste. The influence of sulfide species on the corrosion behavior of the nails was investigated via the thorough description of the modifications undergone by the corrosion products surrounding the metal after re-immersion in deaerated sulfide solution. The only observed modification was the formation of FeS at the corrosion product layer/soil interface. The corrosion product layer, mainly composed of FeCO3, acts as protective barrier, the reactivity of FeCO3 preventing sulfide species to reach the metal and influence the corrosion process.